Abiotic Mechanisms Drive Enhanced Evaporative Losses under Urban Oasis Conditions - Vivoni, Enrique; Perez Ruiz, Eli Rafael; Kindler, Mercedes; Wang, Zhaocheng (2020)
The oasis effect refers to the impact of advected energy on the surface energy balance leading to enhanced evapotranspiration. In this study, we utilize a 1‐yr record of water, energy, and carbon dioxide (CO2) fluxes to study the occurrence and signature of the oasis effect in an irrigated turf grass of an arid urban region. Days with the oasis effect are selected using readily available air temperature and relative humidity and include excessive heat warnings. During oasis days, higher evaporative cooling is demonstrated throughout the day, especially for late afternoons when it can exceed net radiation. Evaporative enhancements are linked to abiotic mechanisms, such as soil and irrigation water evaporation, since plant productivity is unaltered. Nighttime evaporative losses and CO2 releases are also enhanced during oasis days. Our findings show how the oasis effect impacts the water, carbon, and thermal conditions of urban parks.